Nine nights of power: durga, dolls, and darbars - Hüsken, Ute; Narayanan, Vasudha; Zotter, Astrid (SUNY series in Hindu studies, 2021)
Explores the rich diversity of narratives, rituals, and participants connected with one of the most important celebrations for Hindus in South Asia and in the diaspora.